Mekanisme Pembiayaan Qardhul Hasan untuk Meningkatkan Pemberdayaan Ekonomi Guru Perempuan - Hidayati MZ, Hikmatul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the mechanism of Qardhul Hasan financing as an instrument for empowering female teachers’ economic capacity within the Islamic microfinance institution Baituttamkin in West Nusa Tenggara. The dual role of female teachers as educators and family economic supporters requires fair access to financing based on Islamic principles. Through the Qardhul Hasan scheme, the institution provides interest-free loans intended for developing community-based microenterprises. This research employs a qualitative approach using field research and descriptive-analytic methods. Data were collected through observation, interviews, and documentation at Baituttamkin Aikmel Unit. The findings reveal that the Qardhul Hasan mechanism effectively enhances the economic independence and welfare of female teachers through sharia-compliant business capital support. Beyond financial benefits, the program also serves as a medium for financial education, spiritual strengthening, and fostering social solidarity among participants. Therefore, Qardhul Hasan represents a financing model that not only promotes material prosperity but also embodies the ethical, equitable, and inclusive principles of Islamic economic values.